Decreased plasma gelsolin in the COVID-19-related acute respiratory distress syndrome - Gunturk Inayet; Seydel Gonul Seyda; Yazici Cevat; Topaloglu Ulas Serkan; Eren Esma; Yuksel Recep Civan (Türk Biyokimya Dergisi)
The aim of this study was to evaluate the potential roles of plasma gelsolin (pGSN), transforming growth factor-beta1 (TGF-β1), and lysophosphatidic acid (LPA) as profibrotic and immune modulatory markers in patients with acute respiratory distress syndrome (ARDS) and patients with mild to moderate disease.